Unravelling the Dynamic Physiological and Metabolome Responses of Wheat (Triticum aestivum L.) to Saline–Alkaline Stress at the Seedling Stage - Wei Ren; Li Chen (Metabolites)
Background/Objectives: Understanding metabolome adjustment under saline–alkaline conditions is crucial for enhancing crop tolerance capacity and ensuring food security. Although soil salinization impairs wheat seedlings’ growth, metabolome plasticity under saline–alkaline stress remains poorly understood. Here, we delved into dynamic physiological and metabolome shifts in wheat seedlings grown on SAS (saline–alkaline soil) on the 7th and 15th days post-germination (DPG). Methods: A self-developed and cultivated high-generation salt–alkali wheat variety (011) was grown on SAS and control soil, followed by comparative physiological, biochemical, and metabolomics analyses of seedlings. Results: The seedlings’ saline–alkaline stress responses were developmentally regulated with reduced growth, increasing accumulation of proline and soluble sugars, and differential antioxidant response. LC-MS-based global metabolomics analysis revealed significant metabolite profile differences, with 367 and 485 differential metabolites identified on the 7th and 15th DPG, respectively, between control and treatment. Upregulation of saccharides, flavonoids, organic acids (citrate cycle-related), phenolic acids, amino acids and derivatives, phytohormones, and sphingolipid metabolism was essential for seedlings’ growth on SAS. The key induced metabolites in seedlings grown on SAS include saccharic acid, trehalose, sucrose, glucose, L-citramalic acid, phellodendroside, scutellarin, anthranilate-1-O-sophoroside, lavandulifolioside, N-methyl-L-glutamate, etc. Up-regulated phytohormones include abscisic acid (3.8-fold, 7th DPG and 3.18-fold, 15th DPG), jasmonic acid (1.93-fold, 15th DPG), and jasmonoyl isoleucine (2.03-fold, 15th DPG). Conclusions: Our findings highlight the importance of ABA and jasmonic acid in regulating salt–alkali tolerance in wheat seedlings. Moreover, this study depicts key pathways involved in salt–alkali tolerance in wheat seedlings and unveils key DMs, offering resources for boosting wheat production on SAS.